The hRing: A wearable haptic device to avoid occlusions in hand tracking - Pacchierotti, Claudio; Salvietti, Gionata; Hussain, Irfan; Meli, Leonardo; Prattichizzo, Domenico (IEEE Haptics Symposium, 2016)
The wearable electronics business has powered over 14 billion in 2014 and it is estimated to power over 70 billion by 2024. However, commercially-available wearable devices still provide very limited haptic feedback, mainly focusing on vibrotactile sensations. Towards a more realistic feeling of interacting with virtual and remote objects, we propose a novel wearable cutaneous device for the proximal finger phalanx, called "hRing". It consists of two servo motors that move a belt placed in contact with the user's finger skin. When the motors spin in opposite directions, the belt presses into the user's finger, while when the motors spin in the same direction, the belt applies a shear force to the skin. Its positioning on the proximal finger phalanx improves the capability of this device to be used together with unobtrusive hand tracking systems, such as the LeapMotion controller and the Kinect sensor. The viability of the proposed approach is demonstrated through a pick-and-place experiment involving seven human subjects. Providing cutaneous feedback through the proposed device improved the performance and perceived effectiveness of the considered task of 20% and 47% with respect to not providing any force feedback, respectively. All subjects found no difference in the quality of the tracking when carrying out the task wearing the device versus barehanded.